Sur la distribution des valeurs de la fonction d’Euler - Tjan, M. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: М. М. Тян. К вопросу о распределении значений функции Эйлера φ(n) M. Tian. Eulerio funkcijos φ(n) reikšmių pasiskirstymo klausimu